Post-Nephrectomy Lumbar Hernia: A Rare Case and Surgical Repair Using Posterior Component Separation Technique - Jadhav, Mahesh; Tribhuvan , Madhuri (Journal of Neonatal Surgery, 2025)
Lumbar hernia, a rare abdominal wall defect, usually present following surgery. We describe a case of a 50-year-old obese woman who presented with a gradually progressive, reducible swelling in the left lumbar region. One year back, she had undergone open nephrectomy for staghorn calculus. Progressively, the swelling became irreducible over the past month, necessitating further evaluation. Clinical examination along with contrast-enhanced CT suggested a left-sided posterolateral abdominal wall defect (11×9 cm) with small and large bowel loop herniation and absence bowel strangulation. Based on the findings and large defect size, posterior component separation surgery was done with lightweight polypropylene mesh placed retromuscularly and secondary mesh repair for external oblique aponeurosis. The patient had an uneventful postoperative course and was asymptomatic with no recurrence at 5-month follow-up. This case emphasizes the criticality of early diagnosis and customized surgical repair in the management of lumbar hernias following a nephrectomy